The universe in a nutshell - Hawking, S. W. (Stephen W.); Hawking, S. W. (Stephen W.) (London : Bantam, 2001)
"One of the most influential thinkers of our time, Stephen Hawking is an intellectual icon, known not only for the adventurousness of his ideas but for the clarity and wit with which he expresses them. In this new book Hawking takes us to the cutting edge of theoretical physics, where truth is often stranger than fiction, to explain in laymen's terms the principles that control our universe." "The Universe in a Nutshell is essential reading for all of us who want to understand the universe in which we live. Like its companion volume, A Brief History of Time, it conveys the excitement felt within the scientific community as the secrets of the cosmos reveal themselves."--BOOK JACKET.
Includes index.
Keywords: Cosmology -- Popular works